Être à la barre, être accusé(e) - Catherine Lutard-Tavard (Socio, 2014)
Without it being a deliberate choice, the sociologist can be led to work on a subject which is more polemical than others. This happened to me with the analysis of the nationalisms in Yugoslavia in the 1990s – a theme which led to passionate debates even in France. On the basis of a personal experience (a lawsuit for defamation), this article shows the move from science to justice, the conditions to challenge the right to be polemical and shows how legal adjustments, which are increasingly numerous, prove harmful for the development of research and, in particular on ‘sensitive’ issues.